In Vitro Digestion of Grape Seed Oil Inhibits Phospholipid-Regulating Effects of Oxidized Lipids - Sarah Fruehwirth; Sofie Zehentner; Mohammed Salim; Sonja Sterneder; Johanna Tiroch; Barbara Lieder; Martin Zehl; Veronika Somoza; Marc Pignitter (Biomolecules, 2020)
The intake of dietary lipids is known to affect the composition of phospholipids in gastrointestinal cells, thereby influencing passive lipid absorption. However, dietary lipids rich in polyunsaturated fatty acids, such as vegetable oils, are prone to oxidation. Studies investigating the phospholipid-regulating effect of oxidized lipids are lacking. We aimed at identifying the effects of oxidized lipids from moderately (18.8 ± 0.39 meq O2/kg oil) and highly (28.2 ± 0.39 meq O2/kg oil) oxidized and in vitro digested cold-pressed grape seed oils on phospholipids in human gastric tumor cells (HGT-1). The oils were analyzed for their antioxidant constituents as well as their oxidized triacylglycerol profile by LC-MS/MS before and after a simulated digestion. The HGT-1 cells were treated with polar oil fractions containing epoxidized and hydroperoxidized triacylglycerols for up to six hours. Oxidized triacylglycerols from grape seed oil were shown to decrease during the in vitro digestion up to 40% in moderately and highly oxidized oil. The incubation of HGT-1 cells with oxidized lipids from non-digested oils induced the formation of cellular phospholipids consisting of unsaturated fatty acids, such as phosphocholines PC (18:1/22:6), PC (18:2/0:0), phosphoserine PS (42:8) and phosphoinositol PI (20:4/0:0), by about 40%–60%, whereas the incubation with the in vitro digested oils did not affect the phospholipid metabolism. Hence, the gastric conditions inhibited the phospholipid-regulating effect of oxidized triacylglycerols (oxTAGs), with potential implications in lipid absorption.